Bayesian Estimation of the Expected Mean Square Rate of Repeated Measurements Model - et. al., Hayder Abbood Kori , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we consider the estimators corresponding to the expected mean square rate of repeated measurements model depending on Bayes estimation using Jeffreys' non-informative prior and proper Bayes estimation, and obtaining 14 cases that were classified into five types.